Pemanfaatan Teknologi Artificial Intalligance Berbasis Google Gemini untuk Meningkatkan Kemandirian dan Motivasi Siswa dalam Pembelajaran Bola Basket Kelas XI SMAN 2 Mataram - Dandi; Dadang Warta Chanra Wira Kesumah; Kokom Supriyatnak (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to examine the effect of utilizing Google Gemini-based Artificial Intelligence (AI) technology on students' learning independence and motivation in Grade XI basketball learning at SMAN 2 Mataram. The study employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. The research sample consisted of 60 students, divided equally into an experimental group and a control group, with 30 students in each group. Data were collected using learning independence and learning motivation questionnaires and analyzed through descriptive statistics, normality tests, homogeneity tests, and an Independent Samples t-test using IBM SPSS Statistics. The results revealed that the experimental group achieved a higher mean score for learning independence (56.87) than the control group (46.00), with a significance value of 0.004 (p < 0.05). Similarly, the experimental group obtained a higher mean score for learning motivation (63.70) than the control group (52.43), with a significance value of <0.001 (p < 0.05). These findings indicate that the use of Google Gemini has a significant positive effect on improving students' learning independence and motivation in basketball learning. Therefore, Google Gemini can serve as an innovative learning medium to support more active, independent, and student-centered physical education learning.